Year 1 of the ZTF high-cadence Galactic plane survey: strategy, goals, and early results on new single-mode hot subdwarf B-star pulsators. Issue 1 (12th May 2021) - Kupfer, Thomas; Prince, Thomas A; van Roestel, Jan; Bellm, Eric C; Bildsten, Lars; Coughlin, Michael W; Drake, Andrew J; Graham, Matthew J; Klein, Courtney; Kulkarni, Shrinivas R; Masci, Frank J; Walters, Richard; et al.
ABSTRACT: We present the goals, strategy, and first results of the high-cadence Galactic plane survey using the Zwicky Transient Facility (ZTF). The goal of the survey is to unveil the Galactic population of short-period variable stars, including short-period binaries, and stellar pulsators with periods less than a few hours. Between 2018 June and 2019 January, we observed 64 ZTF fields resulting in 2990 deg 2 of high stellar density in the ZTF- r band along the Galactic plane. Each field was observed continuously for 1.5 to 6 h with a cadence of 40 sec. Most fields have between 200 and 400 observations obtained over 2–3 continuous nights. As part of this survey, we extract a total of ≈230 million individual objects with at least 80 epochs obtained during the high-cadence Galactic plane survey reaching an average depth of ZTF– r ≈ 20.5 mag. For four selected fields with 2–10 million individual objects per field, we calculate different variability statistics and find that ≈1–2 per cent of the objects are astrophysically variable over the observed period. We present a progress report on recent discoveries, including a new class of compact pulsators, the first members of a new class of Roche lobe filling hot subdwarf binaries as well as new ultracompact double white dwarfs and flaring stars. Finally, we present a sample of 12 new single-mode hot subdwarf B-star pulsators with pulsation amplitudes between ZTF– r = 20–76 mmag and pulsation periods between P = 5.8–16 min with a strong cluster of systems with periods ≈6 min. All of the data have now been released in either ZTF Data Release 3 or Data Release 4.